Antiviral activity of resveratrol against human and animal viruses - Abba, Yusuf; Hassim, Hasliza; Hamzah, Hazilawati; Mohamed Mustapha, Noordin (Hindawi Publishing Corporation, 2015)
Resveratrol is a potent polyphenolic compound that is being extensively studied in the amelioration of viral infections both in vitro and in vivo. Its antioxidant effect is mainly elicited through inhibition of important gene pathways like the NF-κβ pathway, while its antiviral effects are associated with inhibitions of viral replication, protein synthesis, gene expression, and nucleic acid synthesis. Although the beneficial roles of resveratrol in several viral diseases have been well documented, a few adverse effects have been reported as well. This review highlights the antiviral mechanisms of resveratrol in human and animal viral infections and how some of these effects are associated with the antioxidant properties of the compound.